Production of exopolysaccharide from probiotic Saccharomyces cerevisiae var. boulardii S11 and determination of its structural, rheological, antioxidant and prebiotic properties - Goktas, Hamza; Agan, Cansu; Bekiroglu, Hatice; Bozkurt, Fatih; Sagdic, Osman (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2026)
This study is the first to report the production, characterization, and technofunctional properties of exopolysaccharide (EPS) from the probiotic yeast S. boulardii S11 (Sb-EPS). HPLC analysis revealed that Sb-EPS has a heteropolysaccharide structure composed mainly of mannose and glucose. FT-IR and NMR analyses confirmed the polysaccharide structure of EPS. Rheological analysis showed that Sb-EPS exhibited non-Newtonian shear-thinning flow behavior. The EPS exhibited high antioxidant activity at a concentration of 4 mg/mL, with more than 50% radical scavenging capacity for DPPH and ABTS, and 117.72 +/- 2.54 mg/mL for FRAP. Additionally, Sb-EPS demonstrated 90.11, 71.30, and 55.95% heavy metal adsorption capacities for Cu2(+), Fe2(+), and Zn2(+), respectively. Furthermore, Sb-EPS's ability to stimulate the growth of probiotic bacteria L. rhamnosus and L. plantarum to a greater extent than glucose and inulin suggests its potential as a prebiotic candidate. The findings indicate that Sb-EPS could be a promising, novel, and functional ingredient for food applications.
Keywords: S. boulardii; Exopolysaccharide; Rheological properties; Antioxidant activity; Prebiotic activity; BIOLOGICAL-ACTIVITIES; RHODOTORULA; STRESS; Food Science & Technology